Prevalence of gestational diabetes mellitus and associated factors among women attending antenatal care at Gondar town public health facilities, Northwest Ethiopia - Achenef Asmamaw Muche; Oladapo O. Olayemi; Yigzaw Kebede Gete (BMC Pregnancy and Childbirth, 2019)
Abstract Background Globally, Gestational Diabetes Mellitus (GDM) is rising, but it is a neglected health threat to mothers and their children in low resource countries. Although, GDM is known in Ethiopia, information regarding it remains scarce by recent diagnostic criteria. Therefore, this study aimed to determine the prevalence of GDM and associated factors among women attending antenatal care at Gondar town public health facilities, Northwest Ethiopia. Methods A cross-sectional study was conducted among 1027 pregnant women selected by the systematic random sampling technique. The universal one-step screening and diagnostic strategy was done using a two-hour 75 g oral glucose tolerance test. GDM was diagnosed using updated diagnostic criteria (2017 American Diabetes Association (ADA) or 2013 World Health Organization (WHO) or modified International Association of the Diabetes and Pregnancy Study Groups diagnostic criteria (IADPSG)). Binary logistic regression model was used to identify factors associated with GDM. Results Of the total 1027 pregnant women, 12.8% (95% CI: 10.8–14.8) were diagnosed with GDM. Overweight and/or obesity (MUAC ≥28 cm) (AOR = 2.25, 95% CI: 1.18–4.26), previous history of GDM (AOR = 5.82, 95% CI: 2.57–13.18), family history of diabetes (AOR = 4.03, 95% CI: 1.57–10.35), low physical activity (AOR = 3.36, 95% CI: 1.60–7.04), inadequate dietary diversity (AOR = 1.9, 95% CI: 1.02–3.53), and antenatal depression (AOR = 4.12, 95% CI: 1.85–9.20) were significantly associated with GDM. Conclusions The prevalence of GDM among women attending antenatal care at Gondar town public health facilities was high. Previous history of GDM, antenatal depression, family history of diabetes, low physical activity, overweight and/or obesity and inadequate dietary diversity were significantly associated with GDM. Routine screening of pregnant women and healthy lifestyle are strongly recommended.